Pneumadizee: religiöse Indifferenz als Achillesferse protestantischer Theologie - Nagel, Rasmus (Zeitschrift für Theologie und Philosophie, 2025)
The article reconstructs religious indifference, understood as existential unconcern regarding God, as a problem of pneumadicy. Since Protestant theology answers the question of the genesis of faith pneumatocentrically, the question of indifference towards God, which exacerbates the problem of unbelief, must escalate into a question of pneumadicy. The doctrine of the inner testimony of the Holy Spirit paradigmatically demonstrates the extent to which, in Protestant pneumatology, the Spirit creates existential concern and thus faith. Indifference therefore raises the pneumadicy question of how God can allow man to remain indifferent towards God. This article discusses the various possibilities of pneumadicy and concludes with reflections on the crucified Spirit as the ignored God, showing that death, rather than man’s resistance to God, is the real challenge of pneumadicy.